MODALITAS ‘KEPASTIAN’ NI CHIGAINAI DAN HAZUDA, DAN PADANANNYA DALAM BAHASA INDONESIA - Jiehan Ghenesa Mutiah; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research explains the form and relation, function and meaning of epistemic modality ni chigainai and hazu da,and its equivalent in Indonesian. This analysis based on the concept of modality by Heiko Narrog (2019) and Hasan Alwi (1992). The method that used in this research is descriptive method. As for the results, ni chigainai is used to state the conclusions and beliefs of the speaker to the situation that is in the first proposition, or based on strong evidence. The form of hazu da functions to state the conclusions and beliefs of the speaker based on information with a high degree of certainty or based on strong evidence. The meaning of the use of ni chigainai and hazu da is 'kepastian' with the equivalent of adverb formsaya merasa yakin, saya merasa pasti, pasti, pastinya, tentunya, tentuand niscaya, and adverb pasti, tentunya and tentu; „keharusan‟ with adverb seharusnya, semestinya,and sepatutnya in Indonesian.Key Words: modality, form and relation, function and meaning, equivalent